Effect of Deccox® in a free-choice, grain-mineral mixture on performance of yearlings grazing native range - Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Including Deccox® in a free-choice, intake-limiting, grain-mineral mixture tended to increase grazing stocker gains and substantially reduced the percentage of newly arrived cattle treated for sickness and the number of treatments required per animal.
Keywords: Beef; Deccox®; Bulls; Native grass; Mineral; Health